Chronic and Temporary Exposure to Student Violence Predicts Emotional Exhaustion in High School Teachers. (3rd April 2021) - Olivier, Elizabeth; Janosz, Michel; Morin, Alexandre J. S.; Archambault, Isabelle; Geoffrion, Steve; Pascal, Sophie; Goulet, Julie; Marchand, Alain; Pagani, Linda S.
ABSTRACT: This study investigates the nexus between teacher exposure to student aggression, their level of emotional exhaustion, and the role of belongingness and perceived school safety as mediators. Random-Intercept Cross-Lag Panel Models were conducted among a sample of 2, 072 secondary teachers (57.14% female) from grades 7 to 11 in 77 schools. Chronic levels of exposure to globally high levels of student aggression and specific high levels of direct victimization were associated with increased levels of emotional exhaustion. These associations were fully mediated by teacher perceptions of school belongingness and safety. Temporary fluctuations in witnessing student-to-student aggression led to increased emotional exhaustion via decreased perceptions of safety. Specific levels of witnessing student-to-teacher aggression were not linked with exhaustion over time beyond global levels of exposure to student aggression. The chronicity of exposure to different forms of student aggression is a risk factor for emotional exhaustion among teachers.